WHOLE GENOME SEQUENCING AND GENOTYPING PROTOCOL OF RABIES VIRUS ISOLATES - Yessembekova , G.; Abenova , A.; Amirgazin, A.; Karibayev , T.; Shevtsov , A.; Abdrakhmanov , S. (Eurasian Journal of Applied Biotechnology, 2023)
This study describes the developed protocol for whole genome sequencing of clinical Rabies virus RNA samples on the Illumina MiSeq platform. Previously, genotyping of the rabies virus circulating in Kazakhstan was based on the nucleoprotein gene sequence (N gene). The protocol describes the methods of sample preparation, whole genome sequencing and genotyping currently used for epidemiological analysis not only of Rabies virus, but also for other viral pathogens such as SARS-CoV-2, Influenza and others. The aim of the work was to develop and test a protocol for whole genome sequencing and genetyping of rabies virus isolates for further use in epidemiological monitoring. As a result of the research, whole genome sequences of 31 isolates of Rabies virus isolated from various infected animals and regions of Kazakhstan were obtained for the first time. All the isolates belong to the major steppe-type clade – Cosmopolitan (30 isolates belong to the minor clade CA1, while 1 isolate belongs to an unassigned minor clade). 2 local outbreaks and 6 separated rabies virus lineages were identified. Estimated dates of divergence from a common ancestor were calculated for both the Cosmopolitan clade and the minor clade CA1.